KEANEKARAGAMAN ENZIM INVERTASE, PENGEMBANGAN STRAIN UNGGUL DAN TEKNOLOGI PRODUKSINYA - Wilhelmus Terang Arga Sanjaya; . Giyanto; Rahayu Widyastuti; Dwi Andreas Santosa (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2020)
Invertase Diversity, Novel Strain and Production Technology DevelopmentInvertase or Î²-fructofuranosidase (E.C.3.2.1.2.6) have been a valuable enzyme in food industry, so that research about enhancing invertase activity on an industrial scale has been reported massively. So far, the production of the invertase enzyme is highly dependent on the potential activity of the invertase enzyme derived from microorganisms. The development of enzyme production technology is also a concern in invertase research to obtain an efficient and inexpensive production system. So far, various developments in enzyme production technology and enzyme utilization have been carried out, including various innovations in immobilizing and increasing the stabilization of the invertase enzyme during the production process. The development of superior strains and enzyme production technology continues amid the discovery of the latest approaches such as genetic engineering, protein modification, and nanotechnology. This paper aims to discuss invertase variation from various organisms, its correlation to novel microbial strain development to increase invertase production and invertase enzyme production technologies development including immobilization technology and stabilization of invertase enzymes.Keywords: Î²-fructofuranosidase, ezyme production, fermentation, immobilitation, invertase geneABSTRAKInvertase atau Î²-fructofuranosidase (E.C.3.2.1.2.6) merupakan enzim yang sangat penting dalam dunia industri pangan sehingga berbagai optimasi aktivitas enzim untuk produksi dalam skala industri terus dilakukan. Produksi enzim invertase hingga sejauh ini sangat bergantung oleh potensi aktivitas enzim invertase yang diambil dari mikroorganisme. Selain itu, pengembangan teknologi produksi juga menjadi perhatian dalam pengembangan produksi dan pemanfaatan enzim untuk mendapatkan sistem produksi yang efisien dan murah. Sejauh ini berbagai pengembangan teknologi produksi enzim dan pemanfaatan enzim telah dilakukan, diantaranya dengan berbagai inovasi dalam melakukan imobilisasi dan peningkatan stabilisasi enzim invertase selama proses produksi. Pengembangan strain unggul dan teknologi produksi enzim terus dilakukan di tengah ditemukannya pendekatan-pendekatan terkini seperti rekayasa genentika, modifikasi protein, dan teknologi nano. Artikel ini bertujuan untuk membahas variasi enzim invertase dari berbagai organisme, korelasi pengembangan strain mikrobia unggul terhadap peningkatan produksi enzim invertase, dan perkembangan teknologi produksi enzim invertase meliputi teknologi imobilisasi dan stabilisasi enzim invertase.